Salt precipitation during geological sequestration of supercritical CO2 in saline aquifers: A pore-scale experimental investigation. (September 2021) - Akindipe, Dayo; Saraji, Soheil; Piri, Mohammad
Highlights: CO2 injection at near-wellbore rates induces salt precipitation. Drying is limited by an interplay between advective and diffusive forces. Salt precipitation reduces the pore volume available for fluid flow. Extent of precipitation is affected by CO2 injection rate and rock heterogeneity. Precipitation in micropores is significant especially in clay-bearing sandstone. Abstract: Salt deposition has been encountered in near-wellbore regions of saline reservoirs during field-scale carbon dioxide (CO2 ) sequestration. To explain this phenomenon, pore-scale studies, mostly in the form of micromodel visualizations, have been previously implemented. However, there is limited knowledge about salt deposition and inherent dynamics in reservoir rocks. This study investigates and characterizes the pore-scale evolution of salt precipitation in natural sandstone and carbonate rocks at conditions prevalent in deep saline aquifers. Using x-ray micro-tomography imaging techniques, three evolution stages – advection-dominated, transition, and diffusion-dominated evaporative drying – are delineated. We provide direct evidence for a new mechanism that occurs during the transition from advection to diffusion-limited flow called reverse solute diffusion. This is typified by upward solute diffusion from regions of lower concentrations within the aqueous phase to the highly concentrated evaporating front. Salt deposits eventually form due to solute accumulation at the brine/supercritical CO2 interface. The time and extent of precipitation are influenced by CO2 injection rate and morphological heterogeneity. Specifically, a higher injection rate increases the rapidity of precipitation but causes lower salt deposition. Furthermore, less precipitates form as systems become more homogeneous for the same injection rate. These relationships directly correlate with porosity reduction, leading to a gradual but higher degree of pore plugging in heterogeneous systems.